'Moral distress' – time to abandon a flawed nursing construct?. (February 2015) - Johnstone, Megan-Jane; Hutchinson, Alison
Moral distress has been characterised in the nursing literature as a major problem affecting nurses in all healthcare systems. It has been portrayed as threatening the integrity of nurses and ultimately the quality of patient care. However, nursing discourse on moral distress is not without controversy. The notion itself is conceptually flawed and suffers from both theoretical and practical difficulties. Nursing research investigating moral distress is also problematic on account of being methodologically weak and disparate. Moreover, the ultimate purpose and significance of the research is unclear. In light of these considerations, it is contended that the notion of moral distress ought to be abandoned and that concerted attention be given to advancing inquiries that are more conducive to improving the quality and safety of moral decision-making, moral conduct and moral outcomes in nursing and healthcare domains.